Digital Technologies in Compulsory Musical Education: A Scoping Review (2020-2024) - Hernández-Marín, José Luis (2025)
This scoping review examines the integration of digital technologies in compulsory music education during the 2020-2024 period. Following the PRISMA-ScR protocol, the available evidence was mapped through the analysis of 22 empirical studies, identifying the pedagogical use of 48 tools across early childhood, primary, and secondary education. The findings reveal a predominance of technologies oriented toward music creation, such as digital audio workstations (GarageBand, Soundtrap, BandLab), followed by applications for performance (NoteWorks, Smart Music) and listening (Auralia, EarMaster). The scientific output, concentrated in Europe and led by Spain, reflects an emerging and uneven geographical distribution. Gamification, cooperative learning, and the flipped classroom, aligned with constructivist and sociocultural approaches, are among the most frequent methodologies. Although the evidence suggests positive impacts on students’ motivation, creativity, and autonomy, significant structural barriers persist: the digital divide, insufficient teacher training, and technological limitations. It is concluded that the effectiveness of these technologies depends on the precise alignment between curricular objectives, teachers’ digital competencies, and institutional policies that ensure equitable access. Finally, future research lines are proposed, focusing on generative artificial intelligence, inclusion, and early childhood education.